Potential use of rosemary extract to increase the quality and safety of rendered chicken fat - Badrul, S.; Jaafar, Ahmad Haniff (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
A commercial rosemary extract was evaluated for antioxidant effectiveness in rendered chicken fat and antibacterial activity against selected foodborne pathogens. Four treatments were used in the experiment comprising of 25 and 50 ppm rosemary extract (RE), 200 ppm butylated hydroxyanisole (BHA; commercial antioxidant as positive control), and a negative control without antioxidant. All treatments were subjected to oxidative stability analysis tests including free fatty acid (FFA), peroxide value (PV), p-Anisidine value (AV), and total oxidation value (TOTOX), which were analysed weekly for a total period of seven weeks. In addition, RE was tested for antibacterial activity against Bacillus cereus, Escherichia coli, Klebsiella pneumoniae, Listeria monocytogenes, Salmonella enterica, and Staphylococcus aureus using disc diffusion assay (DDA). The results showed that the addition of 50 ppm of RE yielded the most potent antioxidant effect as evidenced by the lowest amounts for negative oxidation indicators (i.e., FFA, PV, AV, and TOTOX) as compared to the other treatments. BHA showed significant antioxidant effect between treatments for FFA and PV, and 25 ppm RE showed significant antioxidant effect between treatments for FFA only. DDA resulted in inhibition zones against all the tested bacteria ranging from 7.7 ± 0.6 mm (S. enterica; weakest inhibition) to 11.8 ± 0.4 mm (K. pneumonia; strongest inhibition). The findings showed that rosemary extract can be used as a natural antioxidant that effectively delays oxidation and exhibits antibacterial properties.